Using Markov Chain to Forecast Stock Price Movement in The Iraq Stock Exchange - Odah, Sabbar Thijeel (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2025)
The purpose of this paper is to apply "Markov chain" modeling to the Iraq Stock Exchange Index (ISX60) over a period of 231 trading days, from January 02, 2024, to December 30, 2024. The prediction was made by identifying three cases of stock price movement: height, low, and stability. The transition matrix and probability vector for the Markov chain were created, and the results showed that the probability of a decrease in the Iraq Stock Exchange Index prices was the highest, reaching (0.489), the probability of a rise in prices was the lowest, reaching (0.177), and the probability of stock price stability was (0.33). The purpose of this study was to raise local investors' understanding of the Markov chain model's predictive power to aid in investment decision-making.